Factors Influencing the Intention to Purchase Smart Home Devices in Generation Y - Camta, Moragot; Tongngam, Sutep (NIDA Development Journal, 2024)
The objective of this quantitative research is to study the factors influencing the intention to purchase smart home devices in generation Y by collecting the online survey of 400 samples in Thai-land. In order to prove the hypothesis, path analysis has been used to process the data. According to the statistics results, it is obvious that the perceived value directly influences the intention to purchase. The results also reveal that the most positive influencing factor for the people in generation Y is the perceived enjoyment, followed by the perceived compatibility and the perceived usefulness, respective-ly. On the other hand, the most negative one is the perceived fee, followed the perceived technicality. Compared to the literatures, the outputs are consistent with most of them. In term of benefit, business-es could arrange their smart home device campaigns based on the influencing factors to achieve the intention to purchase of their target customers in generation Y.